2021
DOI: 10.3389/fpsyg.2021.584760
|View full text |Cite
|
Sign up to set email alerts
|

From Physical Activity Intention to Behavior: The Moderation Role of Mental Toughness Among College Students and Wage Earners

Abstract: This study explored the correlation between mental toughness (MT) and physical activity (PA), and the moderation role between PA intention and subsequent behavior among college students and wage earners. Five hundred ninety-one college students (251 male, 340 female) aged from 19 to 24 and 285 (157 male, 127 female) wage earners aged from 27 to 58 recruited from seven colleges and five cities in China. A Theory of Planned Behavior (TPB) questionnaire, MT Inventory, and the International PA Questionnaire was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…The initial search yielded 822 hits, with 698 after the removal of duplicates ( Figure 1 ). After title and abstract review, 41 full-text articles were assessed for eligibility, and 33 studies met the inclusion criteria and were retained in the final review [ 16 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The majority of the studies utilized a noncontrolled timeseries or pre-post design, with follow-up periods ranging from 1 week to 6 months ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search yielded 822 hits, with 698 after the removal of duplicates ( Figure 1 ). After title and abstract review, 41 full-text articles were assessed for eligibility, and 33 studies met the inclusion criteria and were retained in the final review [ 16 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The majority of the studies utilized a noncontrolled timeseries or pre-post design, with follow-up periods ranging from 1 week to 6 months ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of seven studies assessing personality traits as moderators in the intention–behavior pathway, two studies found statistically significant moderators [ 45 , 46 ], while five studies did not [ 47 , 48 , 49 , 50 , 51 ] ( Table 1 and Table 2 c, and Figure 3 ). De Bruijn et al [ 46 ] assessed neuroticism and conscientiousness, which are two traits from the Five-Factor Model of Personality (FFM), and found that neuroticism moderated the intention–fruit consumption gap, such that lower neuroticism led to a stronger relationship between intention and behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies that have noted the importance of the TPB to observing and explaining human behavior and helps to understand how people change or modify behavior [24]. In general, the finding of this study indicated that the overall means of attitudes, subjective norms, and perceived behavioral control for all participants toward participation in physical activity were (5.18 out of 7.00), (3.41 out of 5.00), and (3.55 out of 5.00) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We further asked if females reported lower MT scores, compared to male participants, and the answer was no. Previous studies showed that MT scores were associated with higher physical activity and exercise scores [ 30 , 47 , 48 , 51 , 63 , 64 , 76 , 77 , 78 ] and that such physical activity and exercise levels were associated with dimensions of psychological functioning. Given this, it is conceivable that the sample of active young adults was too homogeneous in their physical activity levels and psychological functioning, such to preclude higher statistical variance and thus a more meaningful pattern.…”
Section: Discussionmentioning
confidence: 99%